Pengaruh Kandungan Serbuk Grafit terhadap Kekerasan dan Densitas pada Paduan Serbuk Logam Fe-Cr. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Metal matrix composites can be produced by powder metallurgy (P/M) route. Product of P/M generally has porosity that affects physical and mechanical properties. The aim of this research is to investigate the effect of graphite addition to physical and mechanical properties of Fe-Cr composites. Materials used in this research were Fe-Cr one powder) as a matrix and graphite powder as a reinforcement. The content of the reinforcement are 0